Case Report: Successful Use of Biliary Stent for Iatrogenic Esophageal Perforation Following Balloon Dilation in a 7-Month-Old Infant - Liu, Meng-Chuan; Wang, Yao-Sheng; Yang, Yao-Jong; Lai, Fu-Ping (Frontiers in Pediatrics, 2020)
Esophageal perforation is a rare but critical emergency that requires early detection and prompt management. In the pediatric population, iatrogenic injury is the most common etiology of esophageal perforation, and the majority of cases come from stricture dilation. Treatment options include medical management, endoscopic therapy, and surgery. Usually, conservative treatment is appropriate in most carefully selected patients, especially in the setting of early diagnosis and with the absence of severe sepsis. A surgical approach is reserved for a large tear, intrapleural leak, or clinical deterioration after unsuccessful conservative management. With the advancement of the endoscopy technique, endoscopy therapy using esophageal stents is an available choice for adult populations who are complicated with a protracted healing course or comorbidities precluding surgical attempts. However, this procedure is seldom implemented in children, especially young infants, owing to unavailable equipment and experts. We report our successful use of a fully covered self-expandable metal biliary stent in managing esophageal perforation in a seven-month-old infant. Since encouraging achievement, this model can be applied to more children who have the same problem.